Philosophy in late antiquity : boundaries of being - Vergeer, Charles (Cambridge Scholars Publishing, 2019)
Late Antiquity seems to retreat in silence. However, Nietzsche drew attention to the fact that what we know about antique philosophy are not the voices of Plato or Aristotle that once sounded in Athens, nor those of Cicero or Seneca in Rome. They have come to us as perceived by the authors of the waning of the classical world, the world of Late Antiquity. This was a world about to perish, characterised by the decline of the Roman Empire and its legal system, and the tensions between the philosophy and paganism of Antiquity and Christianity. The medieval and our contemporary world are based on.